Patient-reported outcome instruments used in immune-checkpoint inhibitor clinical trials in oncology: a systematic review - Sara Colomer-Lahiguera; Denise Bryant-Lukosius; Sarah Rietkoetter; Lorraine Martelli; Karin Ribi; Donna Fitzpatrick-Lewis; Diana Sherifali; Angela Orcurto; Rosalyn Juergens; Manuela Eicher (SpringerOpen, 2020)
Abstract Context Immune-checkpoint inhibitors (ICI) have shown significant benefits for overall survival across various cancer types. Patient-reported outcomes (PROs) are assessed in clinical trials as a measure of efficacy. However, it remains unclear to what extent current PRO instruments capture symptoms specific to ICI toxicities. We conducted a systematic review to identify the use and content validity of PRO instruments in ICI clinical trials in oncology. Methods Literature was retrieved from PubMed, Embase, PsycINFO, Medline and CINAHL databases. Articles presenting ICI clinical trials' PRO results, clinical trial study protocols, and conference abstracts stating the use of PRO measures were assessed. We evaluated the validity of identified instruments by comparing their symptom-related content with the adverse events reported in each ICI clinical trial. Results From database inception until January 2020, we identified 191 ICI clinical trials stating the use of PRO measures of which 26 published PRO results. The cancer-specific EORTC QLQ-C30 and the generic EQ-5D questionnaires were the most widely used instruments, often in combination with disease-specific PROs. Instruments used to report PRO symptom-related toxicities covered 45% of the most frequently reported AEs, whereas 23% of AEs were partially covered and 29% were not covered at all. Of non-covered AEs, 59% referred to the dermatologic system. Partially covered AEs related to endocrine and specific types of pain. Conclusion Despite the high frequency of symptom-related toxicities related to ICI, these events are only partially covered (or not addressed) by current PRO instruments, even when combined. Further research is needed to develop new strategies to tailor PRO instruments to specific ICI toxicities.